In vitro activity of ten medicinal plants on ten Streptococcus pneumoniae strains - Guevara Duncan, J. M. (2012)
Introduction: The healthy carrier is the main disseminator of pneumococcal infections through nasopharynx; an alternative for treatment is a medicinal plant. Objectives: To determine the effectivity of ten medicinal plants against Streptococcus pneumoniae. Design: In vitro experimental study. Biologic materials: Medicinal plant extracts and Streptococcus pneumoniae strains. Interventions: Ten medicinal plant extracts were put in contact in vitro with 10 different Streptococcus pneumonia strains. Main outcome measures: Medicinal plant extracts activity against Streptococcus pneumoniae strains. Results: Only almendro y Bellaco caspi showed small inhibition halos with some strains; with almendro two of 10 Pneumococcus strains were inhibited and with Bellaco caspi seven strains were inhibited and three were resistant. These results had no relation either with Pneumococcus serotype or with antibiotics used according to antibiograms. Conclusions: Bellaco caspi could be an alternative for treating nasopharynx Pneumococcus, but due to resistance to three Streptococcus pneumonia strains there is no total guarantee and an antibiogram for pneumococci against medicinal plants is needed.